(untitled) (Baghdad Science Journal, 2019)
Iraq has the second largest proven oil reserves in the world. According to oil experts, it is expected that the Iraq’s reserves to rise to 200+ billion barrels of high-grade crude. Oil is a strategic commodity for producing and exporting countries in general, and Iraq in particular, as demonstrated by the international experience that oil is an important means to achieve economic growth, an important tool in the overall economic, social and political development. It is also an important source of hard currency for any national economy and a means to connect the local economy and the global economy. In this paper we focus our attention on selecting the best regression model that explain the effect of human capital represented by different levels of human cadres on the development of the Iraqi oil industry by employing the data of a time series consisting of 21years period. Two popular classical procedures were applied to select such model, specifically, all possible regression procedure and the stepwise regression procedures. The statistical program SPSS was employed to perform the required calculations.